Soil compaction from off-road transportation machine on tropical hill forest land - Jusoff, Kamaruzaman (Universiti Pertanian Malaysia, 1988)
Bulk densities of the upper 15 cm of soil under a crawler tractor track increased by an average of 54.0% to 1.52 g/cm3; the increase was 37.0% and 24.0% for the soil between the tracks compacted by the skidding of logs and berm, respectively compared to those of adjacent undisturbed soils two years after logging. Macroporosity was reduced 21.2% for the soil in the track; 14.0% for log-disturbed and 9.0% for the berm. Micropore spaces of soils in the track, log-disturbed and berm increased by 80.0, 60.0 and 20.0%, respectively. Compaction significantly reduced the total porosity of track soil, log-disturbed soil and berm by 20.4%, 13.4% and 8.8%, respectively compared to that of undisturbed soil Resistance to penetration of soils in the track for the upper 15 cm soil depth increased 10 fold over that of the undisturbed soil. This information should facilitate decisions concerning off-road transportation, machine-track or tire configuration and seasonal traffic programme management, to reduce the chances of compaction.